Analysis of the Financial Performances of Banks with the TOPSIS Method Weighed by Entropy - Karahan, Mehmet; Kızkapan, Lokman; Dinç, Hasan (Springer Science and Business Media Deutschland GmbH, 2023)
The competition conditions, which are getting more and more difficult in our age, made it inevitable to constantly monitor the performance of banks, which is one of the most important elements of the financial system. The ruthless competition environment forces bank to use the resources they have in the most efficient way. Therefore, it is very important for banks to evaluate their own performance and take measures to increase their performance in line with the evaluation results. The aim of this study is to comparatively analyse the financial performances of the top five banks operating in Turkey in 2020, which have the highest profit ratio in terms of asset size, for four quarters. Performance evaluation of banks was made using 9 criteria and the success of the management strategies followed by the banks throughout the year was evaluated by monitoring the performance rankings in four periods. According to the results obtained from the study; Ranking first in the financial performance ranking of the five banks analysed, Ziraat Bank raised its score from 0.62 in the first quarter to 0.75 points in the second quarter, and managed to maintain its first place performance until the end of the year, despite falling to 0.60 points in the third quarter. The performance increase of this bank in the first place in the second quarter, which is the crisis period, was interpreted as turning the crisis into an opportunity. While the performance score of the other bank, which ranked second in the first quarter, was 0.56, it decreased to 0.37 points in the second quarter and increased again to 0.50 points in the third quarter. The continuation of this bank's second place performance throughout the year was interpreted as demonstrating a stable performance management, but not being able to take advantage of the opportunities in the second quarter and its performance declined, but showed a rapid recovery in the third quarter. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
22nd International Symposium for Production Research, ISPR 2022 -- 6 October 2022 through 8 October 2022 -- Antalya -- 291539
Keywords: ENTROPI; Financial performance; Multi criteria decision making; TOPSIS; Turkish banking sector